Characterization of chitinase from Shewanella inventionis HE3 with bio-insecticidal effect against granary weevil, Sitophilus granarius Linnaeus (Coleoptera: Curculionidae). (October 2020) - Laribi-Habchi, Hassiba; Bouacem, Khelifa; Allala, Fawzi; Jabeur, Fadoua; Selama, Okba; Mechri, Sondes; Yahiaoui, Merzouk; Bouanane-Darenfed, Amel; Jaouadi, Bassem
Graphical abstract: Highlights: A chitinase CHiA-Si40 with molecular mass of ∼40 kDa was purified and characterized. The optimum pH and temperature values for activity were pH 4 and 70 °C, respectively. It displayed higher performance than ChiA-Hh59, Chitodextrinase®, and ChiA-65 enzymes. Good candidate for chitin-degradation and bio-insecticidal agent for Sitophilus granaries. Abstract: A 40 kDa chitinase from Shewanella inventionis HE3 was purified (ChiA-Si40) and characterized. Using fermentor with an optimized medium for 48 h at 37 °C, enzyme activity was enhanced by 10-times compared to those using shaking-flask-culture. Purified chitinase is a homogenous monomer with molecular mass of 40 kDa. Its N-terminal residues revealed significant identity with glycoside hydrolase family 18 (GH18) chitinases from Gammaproteobacteria . Using colloidal chitin as a substrate, its finest activity was accomplished at pH 4 and a temperature of 70 °C. Its catalytic efficiency ( k cat / K m ) was superior to that of some bacterial GH18 chitinases and commercial enzyme, Chitodextrinase®. For scale-up and with regards to the improvement of ChiA-Si40 with PEG 6000 storage stability (6 months), the atomizing process was more pronounced than that of lyophilizing. Bio-assay of ChiA-Si40 against grain weevil Sitophilus granarius, indicates that it had an efficient insecticidal effect. About 10–100 % mortality rates were obtained 1-h after insect came in contact with ChiA-Si40. Histological study clearly demonstrated that luxury larval mid-gut, peritrophic-membrane, and epithelial-cells have been affected considerably after ChiA-Si40 treatment. These properties make ChiA-Si40 a potential bio-insecticidal agent for the biological control of S. granarius that is popular among insect pests of stored grains in Algeria.